Desempenho do camarão marinho Litopenaeus vannamei (Boone,1931) cultivado com uso de probióticos quando submetido à infecção com Vibrio harveyi - DANTAS, Danielli Matias de Macêdo (2008)
The fast expansion of farmed shrimp industry during the last decades has been offering high profitable deal to many countries. However, diseases appearing have caused lots of serious economic damage on productive sector. The effect of probiotic in Litopenaeus vannamei juveniles when submitted to the infection by Vibrio harveyi was evaluated in the present study The exposure to V. harveyi was carried out during 15 days using individuals reared for one month in a closed recirculation system with a commercial probiotic (Bacillus sp.) added to water and food (PAR), only in the water (PA), only in food (PR) and without probiotic (SP). Were examined the responses of food consumption, total concentration of hemocytes, growth and survival. The food consumption did not differ significantly among the treatments, but in the SP treatment a significant reduction occurred in the second week. The PAR and PA treatments showed inferior and more constants values in the total hemocits concentrations during the experimental period. The highest growth rates were observed in the PAR (0.34 ± 0.19 g/week) and SP (0.45 ± 0.04 g/week) treatments, but did not differ statistically within these treatments. Shrimp survival values were higher than 98% in all treatments. The results suggest that the addition of Bacillus sp. to the water or food separately, could increase the food consumption during a longer period of time in shrimp infected by V. harveyi and interfere positively in the immune response of L. vannamei.